2012
DOI: 10.5430/bmr.v1n4p63
|View full text |Cite
|
Sign up to set email alerts
|

Whom to Believe: Recruiting Information Source Credibility and Organizational Attractiveness

Abstract: This study uses a policy-capturing methodology to investigate how job seekers faced with conflicting recruiting information make organizational attractiveness judgments. It proposes that when considering recruiting information, the credibility of the information source, in terms of trustworthiness, expertise, integrity, and liking, will be positively related to the extent to which information from each source is used when judging the attractiveness of organizations. The results indicated that some sources are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 51 publications
2
5
0
Order By: Relevance
“…Another issue that is worth noting is the use of Fisher et al's (1979) credibility scale. The discriminant validity check and CFA results not only fully support the results in H2 (for overall source credibility), but are also consistent with Mumford's (2012) proposition that the Fisher et al's three credibility components were all essential elements when an information receiver evaluates the credibility of an information provider. The inter-relatedness of the three components indicates the overall rating of the three components could be considered to represent the overall perception of source credibility.…”
Section: Study Limitations and Future Study Suggestionssupporting
confidence: 79%
See 2 more Smart Citations
“…Another issue that is worth noting is the use of Fisher et al's (1979) credibility scale. The discriminant validity check and CFA results not only fully support the results in H2 (for overall source credibility), but are also consistent with Mumford's (2012) proposition that the Fisher et al's three credibility components were all essential elements when an information receiver evaluates the credibility of an information provider. The inter-relatedness of the three components indicates the overall rating of the three components could be considered to represent the overall perception of source credibility.…”
Section: Study Limitations and Future Study Suggestionssupporting
confidence: 79%
“…These outcomes support Mumford's (2012) propositions that the three components are related and all validly contribute to the overall source credibility perceptions but are also worthy of individual examination (see also Fisher et al, 1979). Therefore, we first view the three factors as 'determinants of credibility' (Fisher et al, 1979, pg.…”
Section: Decision-making Style and Perceived Credibilitysupporting
confidence: 68%
See 1 more Smart Citation
“…Along similar lines, future research that more holistically examines the effects of political climate information on job pursuit intentions (e.g., by simultaneously also considering factors, such as pay or organizational image) would also be informative, especially considering the effect size magnitude of political climate information was smaller in Study 1, where additional job information was presented, relative to Studies 2 and 3, where other job characteristics were not provided. Furthermore, research that integrates other theoretically relevant job search factors identified in prior research (e.g., multiple information sources, conflicting information, and vacancy availability; e.g., Highhouse et al, ; Mumford, ; Saks & Ashforth, ) into our model of politics information and Machiavellianism would also be particularly insightful.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, research that integrates other theoretically relevant job search factors identified in prior research (e.g., multiple information sources, conflicting information, and vacancy availability; e.g., Highhouse et al, 1998;Mumford, 2012;Saks & Ashforth, 1997) into our model of politics information and Machiavellianism would also be particularly insightful.…”
Section: Strengths Limitations and Directions For Future Researchmentioning
confidence: 99%